Evaluation of Cell Death Potential of Lepidium sativum Seed Extracts in MCF-7 Cells and Molecular Docking-based Correlation of Identified Bioactive Components with Human Caspase-6 Protein - R, Rajasekaran; P.K, Suresh (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim and Background: The methanolic extract of Lepidium sativum L. was known for its free radical scavenging potential and anticancer properties. The aim was to perform a comparative investigation of the cytotoxic and cell death potential of the Soxhlet (SOX) and crude methanolic extract (CRU). `Materials and Methods: MTT as well as the PI-based assays in caspase-3-deficient, MCF-7 human breast cancer cells, for its cytotoxic potential and synergistic effect. LC-QTOF-MS/MS was used for characterization. These bioactive molecules were docked with human caspase-6 (2WDP) as well as its zymogen variant (4IYR) to mimicking a more physiological form of cell demise. Results: Both extracts showed a dose-dependent toxicity and the IC50 was found to be 136.75μg/ml, and 88.49 μg/ml compared with that of standard quercetin (8.72μg/ml). At their IC50 concentrations, the corresponding PI-based flow cytometry and cell death values were 31.5±3% and 32.4±5.6, while that of quercetin was 36.9±7.4 %. A synergy in cell death was seen for a combination of L. sativum extracts (CRU-MeOH & SOX-MeOH) and quercetin. Thirteen (13) compounds were reported for the first time in this seed by LC-MS/MS. Good binding affinity was seen with both human caspase -6 (2WDP) and the mutated zymogen (4IYR) with reference to that of quercetin. Conclusion: This in vitro/in silico correlation showed that the methanolic extracts of L. sativum exhibited a significantly higher level of cell death in MCF-7 cells. Also, their synergistic increases in cell death provides a basis possibly for a combination therapy-based strategy.
Keywords: Lepidium sativum L; Crude extract; LC-QTOF-MS/MS; Cell-based toxicity; Cell death potential; In-silico analysis